Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1034/j.1399-302x.2000.150103.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviruses in periodontal pocket and gingival tissue specimens

Abstract: Human cytomegalovirus (HCMV) and Epstein-Barr virus type 1 (EBV-1) are frequently detected in crevicular fluid of deep periodontal pockets, but little or no information is available on occurrence of herpesviruses in gingival tissue. This investigation studied the presence of herpesviruses in periodontal pockets and the corresponding gingival tissues from 11 periodontally healthy and 14 periodontitis sites. A nested-polymerase chain reaction was employed to identify the presence of HCMV, EBV-1, EBV-2, herpes si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
3
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 22 publications
4
143
3
6
Order By: Relevance
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study were at lower levels as compared to some studies done in other countries. 18,[20][21][22][23] This could also be because the detection levels may depend on the virus being in the active or latent stage. The primary infection of the host with herpesvirus is followed by a state of latency and reactivation.…”
Section: A Study Done By Contreras Et Al In American Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceivably, the complexity of the subgingival microbiota of periodontitis may favor the colonization by these "non-oral species". Several studies have reported strong associations between certain pathogens and oral bacterial such as H. pylori and Tannerella forsythia (40), as well as co-infection of herpesviruses with T. forsythia and/or Porphyromonas gingivalis (6,18) in sites with periodontitis. The etiologic role of these pathogenic species and their relationship with oral bacteria in periodontal infections is not fully understood; although these observations might suggest a possible contribution to the etiology of these diseases.…”
Section: Figurementioning
confidence: 99%
“…Also fungal species like Candida albicans (Hannula et al, 1997) are predominant in endodontic and periodontal lesions. Recently it has been found that Cytomegalo virus, Ebstein -barr virus, Herpes virus can also be the causative agents (Contreras et al, 2000).…”
Section: Etiologymentioning
confidence: 99%